NUDGE ON SUSTAINABILITY: A BIBLIOMETRIC ANALYSIS - Putra, Anhar Dana; Musdah, Erwin; Azmi, Ilima Fitri; Sampe, Valentin Laura; Muhammad, Ashar; Umar, Arif Alauddin; Fattah, Sulaeman (Faculty of Administrative Science, Universitas Brawijaya, 2024)
The success rate of strategies for addressing sustainability issues is increasingly dependent on whether changes in public behavior can and will complement the practical solutions that are currently available. Nudge is a novel behavioral change intervention that is being widely used in the ongoing fight against sustainability issues such as energy conservation, sustainable water, food, and fashion consumption. This article explores the most prolific writers, institutions, and nations, in addition to the most cited papers and publications on Nudge and Sustainability, using the Scopus database. Bibliometric analysis is used to describe the bibliographic data, including the total number of publications and citations for 96 papers published between 2011 and 2022. In addition, the article creates a graphical representation of the bibliographic material by mapping journals, keywords, and institutions with bibliographic coupling and co-citation analysis using the VOS Viewer software. The results of the analysis show that studies about nudge and sustainability are currently more focused on the context of pro-environmental behavior which is mostly micro-behavior such as food consumption behavior. The findings are significant in terms of enriching the growing discourse of nudge in the context of sustainability, as well as providing policy recommendations for governments to better address the issues.